Inflammatory Fibroid Polyp: A Rare Benign Tumor of the Alimentary Tract in Children Presenting As Intussusception-Case Report and Review of Literature - Sotirios Siminas; Eyas Qasem; Rajeev Shukla; Richard Turnock (Georg Thieme Verlag KG, 2014)
Abstract Inflammatory fibroid polyp (IFP) represents a rare cause of gastrointestinal polypoid disease in childhood. Τhe lesion has been described by various names beyond the currently accepted term, including "Vanek's tumour," eosinophilic or submucosal granuloma, gastric fibroma with eosinophilic infiltration, inflammatory pseudotumor, and hemangiopericytoma. The etiopathogenesis and origin of the mesenchymal spindle-shaped cells that comprise the polyp remains enigmatic. Recent studies have shown familial occurrence, expression of platelet-derived growth factor receptor (PDGFRA) and oncogenic PDGFRA mutations in the majority of lesions, suggestive of a neoplastic nature. We present a rare case of a 10-year-old boy with an IFP of the terminal ileum, who presented acutely with intussusception and was treated with a right hemicolectomy. Postoperative course was uneventful and the patient has been asymptomatic during follow-up. Histopathology and immunohistochemical analysis excluded inflammatory myofibroblastic tumor (negative for Alk1, desmin, smooth muscle actin [SMA]), gastrointerstinal stromal tumors (GIST) (negative for CD117) and schwannoma (negative for S100). The lesion was positive for CD34 and faintly for vimentin. Despite the classification of IFPs as a mesenchymal benign neoplasm, in the vast majority of cases, surgical excision alone was curative, and no reports exist of a malignant transformation. A cautious approach with periodic surveillance of the affected children seems reasonable though.